2017
DOI: 10.1039/c7ob01731f
|View full text |Cite
|
Sign up to set email alerts
|

Laser flash photolysis of nanocrystalline α-azido-p-methoxy-acetophenone

Abstract: Irradiation of nanocrystals of azide 1 results in a solid-to-solid reaction that forms imine 2 in high chemical yield. In contrast, solution photolysis of azide 1 yields a mixture of products, with 7 as the major one. Laser flash photolysis (LFP) of a nanocrystalline suspension of azide 1 in water shows selective formation of benzoyl radical 4 (λ ∼ 400 nm), which is short-lived (τ = 833 ns) as it intersystem crosses to form imine 2. In comparison, LFP of azide 1 in methanol reveals the formation of triplet alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Quaternary salts contain additional asymmetric and symmetric C-H stretching peaks over amine-functionalized silica, which are located between 2926–2742 cm −1 . N-H stretching peaks, for example, at 3509 cm −1 in DASi, are absent in QDASi due to the methyl quaternization of amine [ 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quaternary salts contain additional asymmetric and symmetric C-H stretching peaks over amine-functionalized silica, which are located between 2926–2742 cm −1 . N-H stretching peaks, for example, at 3509 cm −1 in DASi, are absent in QDASi due to the methyl quaternization of amine [ 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, HEP adsorption on the QDASi surface was confirmed by FTIR analysis ( Figure 2 ). FTIR spectra of store-bought sodium heparin salt and QDASi were compared, and the C=O stretching band at 1712 cm −1 in QDASi-Heparin conjugate confirms the adsorption of the HEP on the QDASi surface [ 31 , 32 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additional vibrational frequencies of both asymmetric and symmetric C-H stretching can be observed in the quaternary salts situated between 3014 and 2690 cm −1 . The N-H stretching frequencies, present in various DE amides (such as at 3473 cm −1 in MADE), disappeared in quaternized salts [46][47][48][49].…”
Section: Preparation and Ir Identification Of Quaternary Ammonium-fun...mentioning
confidence: 99%
“…6 We demonstrated the use of this method in crystals to form radical pairs that yield photoproducts rather than re-form the starting material (Scheme 1). 7 Specifically, irradiating α-azido-acetophenone derivatives in the solid state yields N-methylenebenzamide derivatives. Laser flash photolysis of nanocrystals showed that the photoreaction occurs through α-cleavage to form a benzoyl and methyl azido radical pair.…”
Section: ■ Introductionmentioning
confidence: 99%